2019
DOI: 10.1007/s11845-019-01988-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nursing aids and registered nurses mixed nursing staffing model with different ratios on the nursing outcomes and cost in Neurology and Neurosurgery Center

Abstract: Background This study aimed to investigate the effect of nursing aids (NAs) and registered nurses (RNs) mixed nursing staffing model with different ratios on the nursing outcomes and cost in China. Methods Five thousand and ninety-one patients treated at Neurology and Neurosurgery Center were consecutively recruited in this study and divided into three groups according to the proportion of NAs and RNs: 100% RN group (N = 1756), 90% RN group (N = 1654), and 75% RN group (N = 1681). Nursing outcomes including me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Chang & Wang, 2013;L.-W. Lin et al, 2003) The results of this research revealed that, because of difficulties encountered in recruiting NAs, some Taiwan hospitals are willing to hire NAs without a high school diploma. Like other studies, this study found caregiver certification to be an essential qualification for NAs (L.-W. Lin et al, 2003;Pang et al, 2019;Yang et al, 2015), as differences in education and training significantly influence NA job performance. Lack of standardized education and training for NAs brings about inconsistent care quality and may increase RN workload, as RNs may assume the added burdens of training and supervising NAs (B.-Y.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Chang & Wang, 2013;L.-W. Lin et al, 2003) The results of this research revealed that, because of difficulties encountered in recruiting NAs, some Taiwan hospitals are willing to hire NAs without a high school diploma. Like other studies, this study found caregiver certification to be an essential qualification for NAs (L.-W. Lin et al, 2003;Pang et al, 2019;Yang et al, 2015), as differences in education and training significantly influence NA job performance. Lack of standardized education and training for NAs brings about inconsistent care quality and may increase RN workload, as RNs may assume the added burdens of training and supervising NAs (B.-Y.…”
Section: Discussionsupporting
confidence: 72%
“…A nationwide survey in the United States found unlicensed hospital personnel (ranked from most to least working hours) to include NAs, patient care technicians, surgical technicians, transporters, medical assistants, surgical aides, monitor technicians, and unlicensed graduate nurses (S. Li et al, 2017). Similarly, NAs in Taiwan are mainly responsible for general tasks that do not require a high level of skill or expertise, such as processing hospital admissions and providing physical help to patients (Huang & Lu, 2017;Pang et al, 2019;Yang & Chen, 2018). Employing unlicensed personnel lets professional nurses allocate more of their time to direct care, which pushes forward patient safety and healthcare quality (S. Li et al, 2017).…”
Section: Increased Workload and Shortage Of Nursesmentioning
confidence: 99%
See 2 more Smart Citations
“…It should establish a solid foundation for the treatment and rehabilitation of medical patients. Patients in the neurology department are prone to tension, irritability, low self-esteem, fear of dragging family members, and other emotions as a result of their paralysis and the loss of their self-care abilities and language abilities [ 21 ], which makes them susceptible to anxiety, tension, and irritability [ 22 ]. These negative emotions will often lead patients to give up their treatment.…”
Section: Application and Specific Measures Of Comfort Nursing In Neur...mentioning
confidence: 99%